2023
DOI: 10.3390/jcm12020696
|View full text |Cite
|
Sign up to set email alerts
|

Double Plating for Complex Proximal Humeral Fractures: Clinical and Radiological Outcomes

Abstract: Double plating for proximal humeral fractures (PHF) is an option to increase the primary fixation stability. Clinical data is missing for assessment of clinical and radiological outcome, as well as complications. We retrospectively examined 35 patients with unilateral PHF, who were treated with double plating for PHF between 2013 and 2019. The mean age was 59.5 ± 12 years and the leading fracture type was a varus dislocation (Resch type IV in 55.3%). A head-split was present in 22.9% of the cases. The primary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…Several studies have reported that lack of medial support is a predictor of failure after surgical fixation of proximal humeral fractures [ 11 13 ]. The double-plate technique has been used to improve the quality and stability of the reduction of the medial humeral calcar [ 14 16 ]. But this method requires stripping of more soft tissues and the blood supply around the fracture is difficult to preserve.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported that lack of medial support is a predictor of failure after surgical fixation of proximal humeral fractures [ 11 13 ]. The double-plate technique has been used to improve the quality and stability of the reduction of the medial humeral calcar [ 14 16 ]. But this method requires stripping of more soft tissues and the blood supply around the fracture is difficult to preserve.…”
Section: Introductionmentioning
confidence: 99%